2017
DOI: 10.1016/j.physletb.2016.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Type II shell evolution in A = 70 isobars from the N ≥ 40 island of inversion

Abstract: International audienceThe level structures of 70 Co and 70 Ni, populated from the β decay of 70 Fe, have been investigated using β -delayed γ -ray spectroscopy following in-flight fission of a 238 U beam. The experimental results are compared to Monte-Carlo Shell-Model calculations including the pf+g9/2+d5/2 orbitals. The strong population of a (1+) state at 274 keV in 70 Co is at variance with the expected excitation energy of ∼1 MeV from near spherical single-particle estimates. This observation indicates a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 42 publications
6
28
0
Order By: Relevance
“…Further, although the timing requirements in the data analysis strongly favors population in 70 Ni from the short-lived ≈ 100-ms (6 − , 7 − ) level in 70 Co, a small contribution from the longerlived ≈ 500-ms (3 + ) level could be present. We also note that in a recent study of the decay chain 70 Fe→ 70 Co→ 70 Ni by Morales et al [46], it is suggested that the spin/parity of the longer-lived level could be (1 + , 2 + ).…”
Section: Experimental Details and Data Analysismentioning
confidence: 50%
“…Further, although the timing requirements in the data analysis strongly favors population in 70 Ni from the short-lived ≈ 100-ms (6 − , 7 − ) level in 70 Co, a small contribution from the longerlived ≈ 500-ms (3 + ) level could be present. We also note that in a recent study of the decay chain 70 Fe→ 70 Co→ 70 Ni by Morales et al [46], it is suggested that the spin/parity of the longer-lived level could be (1 + , 2 + ).…”
Section: Experimental Details and Data Analysismentioning
confidence: 50%
“…This phenomenon, widely studied in recent years (see Ref. [11] for a review), may help us to understand the microscopic mechanisms enhancing quantum many-body correlations in exotic nuclei [12][13][14].…”
Section: Introductionmentioning
confidence: 95%
“…The resistance-control force, i.e. the monopole interaction, does not promote the collective mode by itself, but can change the "environment" : the ESPEs are optimized to different collective modes giving rise to a large diversity of phenomena [20,21,23,24,37,38,55,56]. Although the CI calculations can be refined, the overall agreement to experiments suggests the validity of the underlying picture, shifting our basic understanding from the Liquid Drop model including its quantized forms to a more explicit multi-nucleon description with aspects such as shape coexistence, triaxial instability and shell evolution.…”
mentioning
confidence: 99%